PENGARUH KONSENTRASI DAN FREKUENSI PEMBERIAN POC LIMBAH TAHU TERHADAP PERTUMBUHAN DAN PRODUKSI CABAI MERAH (Capsicum annum L.) - Hesty Pratiwi; Adriani Darmawati; Susilo Budiyanto (Universitas Tribhuwana Tunggadewi, 2021)
The purpose of this research was to examine the effect of the concentration and the frequency of tofu wastewater and the interaction between concentration and the frequency of tofu wastewater on the growth and production of red chili (Capsicum annum L.) plants. The method used in this research was a completely randomized design of a factorial pattern. The first factor is the concentration of tofu wastewater which is consists of 5 treatments, namely tofu wastewater (T0), tofu wastewater 25% (T1), tofu wastewater 50% (T2), tofu wastewater 75% (T3), and tofu wastewater 100% (T4). The second factor is frequency tofu wastewater (F) which consists of 3 levels, namely the frequency of tofu wastewater once time during the planting period on 14 days (F1), second times during the planting period which given when the plant is planted 21 and 42 dast (F2), and three times during the planting period, and which given when the plants were 14, 28, and 42 dast (F3) with three replicates. The results showed that the type of tofu wastewater had a significant effect on the age of the first flowers, the total fresh fruit weight, and the total dry fruit weight. The frequency of tofu wastewater offering had a significant effect on the number of fruits planted. No interaction between the types concentrates on the frequency of tofu wastewater to vegetative and generative plant growth. The best result is the age at the first flower, the total weight of fresh fruit, and the dry weight of 100% tofu wastewater. The best number of fruit crops is the frequency of offering tofu wastewater as much as once watering.